Nutrient retention capacity of a constructed wetland in the Cox Creek sub-catchment of the Mt. Bold Reservoir, South Australia - Nor Azman Kasan (University of Adelaide, 2012)
The Cox Creek sub-catchment is located in the Piccadilly Valley, South Australia. It exports disproportionately high loads of nutrients and sediment to the downstream Mount Bold reservoir. The excessive application of inorganic fertilisers to agricultural land in the Cox Creek sub-catchment has enhanced nutrient exports downstream.